REGISTRO DE LA MEMORIA HISTÓRICA DE LA PARROQUIA PUMALLACTA, CANTÓN ALAUSÍ, PROVINCIA DE CHIMBORAZO, PARA SU RECUPERACIÓN SOCIAL- CULTURAL. - Escudero Hidalgo, Luis Paco (2019)
This research will focus on the recovery of the historical memory of the Pumallacta parish in order to preserve the Intangible Cultural Heritage, in which will be exposed the diverse amount of traditions, customs and legends that constitute the abundance that this town has, which due to passing the time and to different factors like: migration, different religions and the acceptance of new customs, has led to the abandonment of cultural identity, for which information provided by the inhabitants was collected and recorded through the National Institute of Cultural Heritage to avoid the excessive loss of immaterial wealth of the Pumallacta parish, within which it was possible to register the most emblematic traditions such as: King of kings, Carnival, Holy Week, Day of the Dead, village bulls and games; and also their traditional foods such as: potatoes with guinea pig, jucho, locro de cuy, canelazo and the traditional games found in this parish such as hopscotch, kite, spinning top, rope, rope, hide and seek. The research is a descriptive type with a qualitative approach, the data for this research was obtained thanks an structured interviews that were made to several local residents in order to recover and thus avoid the definitive loss of these cultural manifestations.